Stationary temperatures in a hollow cylinder with variable thermic conductivity using a Hankel transform - Villalobos, Alfredo (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
In the present work the Hankel generalized finite transform of third class is used to determinate the stationary temperature distribution u(r, z) in a hollow cylinder with variable thermic conductivity.